Comparison of pharmacodynamics and pharmacokinetics of insulin degludec and insulin glargine 300 U/mL in healthy cats - Gilor, C.; Culp, W.; Ghandi, S.; do Carmo Emidio e Silva, J. A. [UNESP]; Ladhar, A.; Hulsebosch, S. (Elsevier, 2019)
Insulin glargine 300 U/mL (IGla-U300) and insulin degludec (IDeg) are synthetic insulin analogs designed as basal insulin formulations. In people, IGla-U300 is more predictable and longer acting compared with glargine 100 U/mL. The duration of action of IDeg in people is > 42 h, allowing flexibility in daily administration. We hypothesized that IDeg would have longer duration of action compared with IGla-U300 in healthy purpose-bred cats. Seven cats received 0.4 U/kg (subcutaneous) of IDeg and IGla-U300 on two different days, >1 wk apart. Exogenous insulin was measured and pharmacodynamic parameters were derived from glucose infusion rates during isoglycemic clamps and suppression of endogenous insulin. The Shapiro-Wilk test was used to assess normality, and normally distributed parameters were compared using paired t-tests. There was no difference between IDeg and IGla-U300 in onset, peak action, or total metabolic effect. On average, time to peak action (TPEAK) of IGla-U300 was 145 ± 114 min (95% confidence interval [CI] = 25–264) longer than TPEAK of IDeg (P = 0.03) and duration of action (TDUR) of IGla-U300 was 250 ± 173 min (95% CI = 68–432) longer than TDUR of IDeg (P = 0.02). The “flatness” of the time-action profile (as represented by the quotient of peak action/TDUR) was significantly greater for IGla-U300 compared with IDeg (P = 0.04). Overall, insulin concentration measurements concurred with findings from isoglycemic clamps. Based on these data, IDeg is not suitable for once-daily administration in cats. The efficacy of once-daily IGla-U300 in diabetic cats should be further investigated.
Keywords: Diabetes mellitus; Isoglycemic clamp